Design And Fabrication Of A Projectionlithography Machine For The Application Of Microfluidic Pattern Using Commercially Available UV LED - Zulkifli, Zikri (Universiti Sains Malaysia, 2018)
In the present work, a 12µm PDMS microfluidic channel are developed using an in-house designed projection lithography machine system. A master pattern was first produce by patterning on microscope slide which is spin coated with SU-8 2002 negative photoresist and exposing it with the in-house projection lithography machine. Using commercially available low power ultraviolet light emitting diode (UVLED) as a medium to expose the photoresist at different height with quartz glass and soda lime glass. A flexible replication of the master mold was produced using heat cured poly-dimethyl-siloxane (PDMS) via cast molding process which can be used repeatedly to fabricate more PDMS microfluidic channel. The scanning electron microscopy measurement of the fabricated microfluidic pattern on the PDMS showed promising result with a good pattern quality and resolution using the commercially available low power UVLED. This work has demonstrated that the projetion lithography machine system using commercially available low power UVLED is a promising technique and tool for fabricating microfluidic structure on flexible substrate for future application.